Carbon‐Coated SnS Nanosheets Supported on Porous Microspheres as Negative Electrode Material for Sodium‐Ion Batteries. Issue 7 (19th May 2020) - Gao, Suning; Yang, Liangtao; Liu, Zaichun; Shao, Jie; Qu, Qunting; Hossain, Masud; Wu, Yuping; Adelhelm, Philipp; Holze, Rudolf
Abstract : SnS has outstanding theoretical capacity and is a promising electrode material for sodium‐ion batteries. However, intrinsic low conductivity and huge volume changes upon sodium extraction/insertion limit its application. Herein, hierarchical hollow carbon spheres covered with S, N‐doped carbon‐coated SnS nanosheets synthesized by a multistep process are reported, including a hard sacrificial template, hydrothermal reaction, and annealing treatment. The prepared C@SnS@C samples are characterized by X‐ray diffraction, scanning electron microscopy, high‐resolution transmission electron microscopy, and X‐ray photoelectron spectroscopy. The nanosized SnS provides capacity; S, N‐doped carbon coating protects the integrated structure. Consequently, due to the compositional and structural merits, the optimized electrode has a high specific capacity of around 420 mAh g −1 at 0.2 A g −1, high rate performance (200 mAh g −1 at 10 A g −1 ), and good cycling stability with 95% (i.e., 305 mAh g −1 at 0.5 A g −1 ) of the initial capacitance after 100 cycles. Kinetic analyses reveal that a substantial capacitive contribution results in better rate performance of the C@SnS@C electrode. Abstract : Carbon‐coated SnS nanosheets supported on porous carbon microspheres are prepared and applied as negative electrode in a sodium‐ion battery. The structural and compositional characteristics of these nanocomposites are discussed with respect to their electrochemical performance. The performance‐limiting issues of volume change and low electronic conductivity are mitigated successfully.